Listeria monocytogenes Cerebritis and Infective Endocarditis in an Immunocompetent Adult: A Rare Clinical Manifestation - Shalini A. Mohan; Zharif Sufyaan (Case Reports in Infectious Diseases)
Cerebritis and infective endocarditis caused by Listeria monocytogenes are very rare. A 56-year-old man presented with slurring of speech and generalized body weakness of 1 week duration. He did not have any past medical history. On systemic examination, he had mild slurring of speech and facial asymmetry and was initially treated for multifocal chronic cerebral infarcts. Listeria monocytogenes was isolated from blood culture on day 5 of admission. A diagnosis of neurolisteriosis was made as contrast-enhanced-computed tomography (CECT) of the brain showed right frontal cerebritis. He was treated with intravenous benzyl penicillin. His general condition was improving until day 13 of hospitalization whereby he developed haemoptysis and severe Type 1 respiratory failure requiring reintubation. An urgent transthoracic echocardiogram revealed a large vegetation at the anterior mitral valve leaflet measuring 2.01 cm. No active arterial bleeding was seen on computed tomography angiography (CTA) of the thorax. Magnetic resonance imaging (MRI) of the brain showed evidence of right frontal cerebritis. He continued to deteriorate and succumbed to his illness after 3 weeks of hospitalization. Clinicians should be aware of such an occurrence and prompt recognition and adequate treatment are necessary in cases of Listeria monocytogenes cerebritis and infective endocarditis as both are deadly entities.